Mungbean DIRIGENT Gene Subfamilies and Their Expression Profiles Under Salt and Drought Stresses - Xu, Wenying; Liu, Tong; Zhang, Huiying; Zhu, Hong (Frontiers in Genetics, 2021)
DIRIGENT (DIR) genes are key players in environmental stress responses that have been identified in many vascular plant species. However, few studies have examined the VrDIR genes in mungbean. In this study, we characterized 37 VrDIR genes in mungbean using a genome-wide identification method. VrDIRs were distributed on seven of the 11 mungbean chromosomes, and chromosome 3 contained the most VrDIR genes, with seven members. Thirty-two of the 37 VrDIRs contained a typical DIR gene structure, with one exon; the conserved DIR domain (i.e., Pfam domain) occupied most of the protein in 33 of the 37 VrDIRs. The gene structures of VrDIR genes were analyzed, and a total of 19 distinct motifs were detected. VrDIR genes were classified into five groups based on their phylogenetic relationships, and 13 duplicated gene pairs were identified. In addition, a total of 92 cis-acting elements were detected in all 37 VrDIR promoter regions, and VrDIR genes contained different numbers and types of cis-acting elements. As a result, VrDIR genes showed distinct expression patterns in different tissues and in response to salt and drought stress.